2012
DOI: 10.1186/1742-2094-9-136
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CCL2 and its receptor CCR2 in the medullary dorsal horn are involved in trigeminal neuropathic pain

Abstract: BackgroundNeuropathic pain in the trigeminal system is frequently observed in clinic, but the mechanisms involved are largely unknown. In addition, the function of immune cells and related chemicals in the mechanism of pain has been recognized, whereas few studies have addressed the potential role of chemokines in the trigeminal system in chronic pain. The present study was undertaken to test the hypothesis that chemokine C-C motif ligand 2 (CCL2)-chemokine C-C motif receptor 2 (CCR2) signaling in the trigemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 74 publications
(98 reference statements)
5
62
3
1
Order By: Relevance
“…Our laboratory and others have previously demonstrated chemokine/ receptor expression (CX3CL1/CX3CR1; CXCL12/CXCR4) (5, 68, 79) and function (CXCL12/CXCR4) (5) associated with urinary bladder inflammation. These results extend previous findings (20,65,76,80,81) by demonstrating that CCL2/CCR2 interactions contribute to inflammation-induced bladder dysfunction and increased referred somatic sensitivity. These studies provide additional support for chemokines/receptors as potential lower urinary tract targets with therapeutic potential in the context of urinary bladder inflammation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our laboratory and others have previously demonstrated chemokine/ receptor expression (CX3CL1/CX3CR1; CXCL12/CXCR4) (5, 68, 79) and function (CXCL12/CXCR4) (5) associated with urinary bladder inflammation. These results extend previous findings (20,65,76,80,81) by demonstrating that CCL2/CCR2 interactions contribute to inflammation-induced bladder dysfunction and increased referred somatic sensitivity. These studies provide additional support for chemokines/receptors as potential lower urinary tract targets with therapeutic potential in the context of urinary bladder inflammation.…”
Section: Discussionsupporting
confidence: 90%
“…To evaluate the effects of CCR2 blockade on bladder function, rats were anesthetized (1-2% isoflurane) and saline or RS504393 (5 M), a highly specific CCR2 receptor antagonist (7,37,81), was intravesically infused for 30 min. Prior to intravesical drug infusion, the bladder was manually emptied using the Credé maneuver.…”
Section: Open Voiding Conscious Cystometry With Continuous Intravesimentioning
confidence: 99%
See 1 more Smart Citation
“…First, nerve injury in mice induces expression of CCL2 astrocytes in the spinal cord and trigeminal nucleus and also upregulates CCR2 in spinal cord neurons 54, 80 . Second, incubation of spinal cord slices with CCL2 very rapidly (within minutes) increases excitatory synaptic transmission, NMDA currents and ERK activation in dorsal horn neurons 54 .…”
Section: Chemokines: Mediators Of Neuron–glial Interactionsmentioning
confidence: 99%
“…6 Although it is almost absent from the normal central nervous system, expression of CCL2 in the spinal cord could be induced following ischemia, neural trauma, and inflammation. [7][8][9][10][11] Similar up-regulation of CCL2 has also been found in the dorsal root ganglion (DRG) subjected to peripheral nerve injury. [12][13][14] A growing amount of evidence has demonstrated that the CCL2/CCR2 axis might play an essential role in neuropathic pain.…”
Section: Introductionmentioning
confidence: 82%